Decoupling of thermoelectric transport performance of Ag doped and Se alloyed tellurium induced by carrier mobility compensation. (28th February 2022) - Wu, Yue; Zhang, Xiaofan; Wang, Boyi; Liang, Jingxuan; Zhang, Zipei; Yang, Jiawei; Dong, Ximeng; Zheng, Shuqi; Zhao, Huai-zhou
Highlights: Ag doping and Se alloying optimize the thermoelectric performance of Te. Se alloying effectively reduces lattice thermal conductivity of Te by refining grain of Te and introducing high density-defects. Ag doping regulates the micro morphology and increases the grain size of Te-Se solid solution. Ag doping successfully compensates the lost carrier mobility due to Se alloying while retains the ability of Te-based matrix to scatter high-frequency (ω) and medium-frequency phonons. Sb doping effectively optimizes the carrier concentration of Te. Abstract: Alloying with Se is proved to be feasible to suppress the lattice thermal conductivity ( κ L ) of tellurium by introducing multidimensional lattice defects. However, extra ionization impurity centers induced by Se alloying are harmful to the electric transport properties of the matrix. In this paper, we propose that the incorporation of Ag could successfully compensate the lost carrier mobility ( μ H ) due to Se alloying through the regulation of microstructure, resulting in the higher power factor (PF) than that of samples without Ag. After composition optimization, the κ L decreased from 1.29 W m −1 K −1 of Te0.99 Sb0.01 to 1.05 W m −1 K −1 of Te0.94 Ag0.02 Se0.03 Sb0.01 at 350 K, while the PF remained unchanged or even slightly increased. Benefit from the synergistic effect of carrier mobility compensation and phonon scattering, a maximum zT of 0.91 at 573 K and an average zT of 0.57 (between 298 and 573 K) are achieved in Te0.94 Ag0.02 Se0.03 Sb0.01 . This work presents a new strategy for decoupling the thermal and electric parameters of Te-based thermoelectric materials. Graphical abstract: Image, graphical abstract